1985
DOI: 10.3758/bf03197689
|View full text |Cite
|
Sign up to set email alerts
|

Deaf signers and serial recall in the visual modality: Memory for signs, fingerspelling, and print

Abstract: This study investigated serial recall by congenitally, profoundly deaf signers for visually specified linguistic information presented in their primary language, American Sign Language (ASL), and in printed or fingerspelled English. There were three main findings. First, differences in the serial-position curves across these conditions distinguished the changing-state stimuli from the static stimuli. These differences were a recency advantage and a primacy disadvantage for the ASL signs and fingerspelled Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 23 publications
(46 reference statements)
11
61
1
Order By: Relevance
“…This effect can also been understood in terms of primary and secondary language codes with auditorily presented words (primary code) giving better recency than printed words (secondary code) which require recoding to primary code in WM (Shand & Klima, 1981). This explanation is supported from by findings from sign language where a recency advantage in deaf native signers has been found for signs over printed words (Bellugi, Klima & Siple, 1975;Krakow & Hanson, 1985). Serial position effects are also found for visually presented items that are not verbally encoded (Hay, Smith, Hitch & Norton, 2007; Smyth, Hay, Hitch & Norton, 2005).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This effect can also been understood in terms of primary and secondary language codes with auditorily presented words (primary code) giving better recency than printed words (secondary code) which require recoding to primary code in WM (Shand & Klima, 1981). This explanation is supported from by findings from sign language where a recency advantage in deaf native signers has been found for signs over printed words (Bellugi, Klima & Siple, 1975;Krakow & Hanson, 1985). Serial position effects are also found for visually presented items that are not verbally encoded (Hay, Smith, Hitch & Norton, 2007; Smyth, Hay, Hitch & Norton, 2005).…”
supporting
confidence: 72%
“…There was no significant difference in the shape of the curves for the EDS and EHN. Previous work has shown that recency effects are modulated by the relationship between modality of presentation and preferred language that can be understood in terms of recoding to primary language modality (Bellugi, Klima & Siple, 1975;Hay, Smith, Hitch & Norton, 2007;Krakow & Hanson, 1985;Rönnberg, Archer & Ohlsson, 1980;Rönnberg, 1982;Shand & Klima, 1981;Smyth, Hay, Hitch & Norton, 2005). Thus, the similarity of the curves for EDS and EHN suggests that similar recoding from easily nameable pictures to primary language modality for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because such mistakes were related solely to sign phonology and completely divorced from sign and sentence meaning, they always resulted in a nonmeaningful response sentence. These phonological lexical changes are the same type of lexical errors as are reported to occur in short-term memory for isolated signs (Bellugi et al, 1975;Krakow & Hanson, 1985;.…”
Section: Methodsmentioning
confidence: 83%
“…In short-term recall of unrelated signs, signers make errors based on the phonological pattern of signs, rather than on the meaning of the signs to be remembered (Bellugi, Klima, & Siple, 1975;Krakow & Hanson, 1985;Poizner, Newkirk, Bellugi, & Klima, 1981). Signers engage in this phonological pattern recognition even when the phonological shape of the stimulus signs appears to consist of pictures (or mime) to naive observers (Poizner, Bellugi, & Tweney, 1981).…”
Section: Sign Language Processingmentioning
confidence: 99%
“…When ASL signs are presented for recall to profoundly and congenitally deaf, fluent users of ASL, recency (Krakow & Hanson, 1985;Shand & Klima, 1981) and suffix effects (Shand & Klima, 1981) are reported. Additionally, Campbell, Dodd, and Brasher (1983) taught a small set of ASL signs to high school students with normal hearing and reported large recency effects.…”
mentioning
confidence: 99%